GP59 A rare cause of 'mitochondrial disorder': cockayne syndrome. (June 2019) - Fisher, Arie; Asghar, Muhammad; Ryan, Stephanie; Lynch, Bryan; Green, Andrew; Knerr, Ina
Abstract : A 16 month old toddler presented with global developmental delay, truncal hypotonia and microcephaly. Her background history was significant for bilateral developmental dysplasia of the hip, recurrent upper respiratory tract infections, conductive hearing loss and a scalp haemangioma. Development had been apparently normal up until 6 months of age. Over the course of her follow-up she developed signs of cerebellar dysfunction including intention tremor and broad based ataxia, chronic feeding difficulties, pigmentary retinopathy and skin photosensitivity. MRI brain at age 2.5 years showed delayed myelination and cerebellar atrophy. A skeletal muscle biopsy revealed reduced activities for the respiratory chain complexes I, II and IV, in particular, in keeping with a mitochondrial condition. After extensive genetic investigations failed to identify the underlying aetiology, an exome sequencing study was carried out and revealed a mutation in the ERCC6 DNA repair gene, consistent with Cockayne syndrome (OMIM # 133540). This is a rare autosomal recessive genetic condition which causes microcephaly, developmental delay and failure to thrive, along with sun sensitivity, tooth decay, bone abnormalities, hearing and vision loss and other symptoms. The patient has been managed with multidisciplinary care and symptomatic treatment, including skin protection, as well as nutritional and multivitamin supplements. She is wheelchair bound and non-verbal but otherwise medically well at age 7 yrs. Many clinical signs seen in patients with Cockayne syndrome are also found in patients with a primary mitochondrial disease. Conversely, secondary dysfunctional mitochondria may also contribute to the phenotype of patients with Cockayne syndrome. Taken together, this case demonstrates the value of exome sequencing in diagnosing and differentiating rare disorders with diverse and overlapping phenotypes, including primary and secondary mitochondrial conditions, which are less likely to be diagnosed on clinical grounds and biochemical investigations alone.